The impacts of culture on social support, communication values, and coping strategies - Chu, Po Sen (Kansas State University, 2007)
This study explored how people perceive and receive social support, react to stress, and value different communication skills across cultures. Three hundred and four American students and 134 Taiwanese students participated. It was predicted that Taiwanese students would utilize social support less and rely on internally targeted control strategies more than would American students. Conversely, it was predicted that both groups would equally favor comforting and ego support from friendship. The results, however, indicated that the groups did not differ on utilizing social support, and Americans favored ego support more than did Taiwanese. Since cross-cultural contacts are encouraged in many fields such as business and academia, the results have pragmatic implications for cross-cultural mutual understanding, international trading, and sojourners' adjustment training.
Keywords: Social support; Cross-cultural; Communication; Coping; Psychology, Social (0451)